Poly(propylacrylic acid)-peptide nanoplexes as a platform for enhancing the immunogenicity of neoantigen cancer vaccines. (November 2018) - Qiu, Feng; Becker, Kyle W.; Knight, Frances C.; Baljon, Jessalyn J.; Sevimli, Sema; Shae, Daniel; Gilchuk, Pavlo; Joyce, Sebastian; Wilson, John T.
Abstract: Cancer vaccines targeting patient-specific tumor neoantigens have recently emerged as a promising component of the rapidly expanding immunotherapeutic armamentarium. However, neoantigenic peptides typically elicit weak CD8 + T cell responses, and so there is a need for universally applicable vaccine delivery strategies to enhance the immunogenicity of these peptides. Ideally, such vaccines could also be rapidly fabricated using chemically synthesized peptide antigens customized to an individual patient. Here, we describe a strategy for simple and rapid packaging of peptide antigens into pH-responsive nanoparticles with endosomal escape activity. Electrostatically-stabilized polyplex nanoparticles (nanoplexes) can be assembled instantaneously by mixing decalysine-modified antigenic peptides and poly(propylacrylic acid) (pPAA), a polyanion with pH-dependent, membrane destabilizing activity. These nanoplexes increase and prolong antigen uptake and presentation on MHC-I (major histocompatibility complex class I) molecules expressed by dendritic cells, resulting in enhanced activation of CD8 + T cells. Using an intranasal immunization route, nanoplex vaccines inhibit formation of lung metastases in a murine melanoma model. Additionally, nanoplex vaccines strongly synergize with the adjuvant α-galactosylceramide (α-GalCer) in stimulating robust CD8 + T cell responses, significantly increasing survival time in mice with established melanoma tumors. Collectively, these findings demonstrate that peptide/pPAA nanoplexes offer a facile and versatile platform for enhancing CD8 + T cell responses to peptide antigens, with potential to complement ongoing advancements in the development of neoantigen-targeted cancer vaccines. Graphical abstract: Image 1